PENGARUH JARAK TANAM TERHADAP JUMLAH MATA TUNAS PADA BEBERAPA KLON KAPUK - SAHID, MOCH.; BUADI, BUADI; FACHRUDIN, O. M.Y. (Jurnal Penelitian Tanaman Industri, 2000)
Effect of plant spacing on the number of buds of capok clonesThe experiment was conducted at Muktiharjo Experimental Farm. Pati from December 1991 to December 1993. The experiment was arranged factorially in a split plot design with three replications. The main plot was plant spacing, i.e. 2 m x I m and 2 m x 2 m, while the sub plot was clones (source of buds), namely MH I. Mil II. logo B, (lanang 36 x Siam) x Congo, (Congo 2 x Lanang). (SS 29 x Congo), (Jepara x Congo 2), and (P. Gudang x Lanang) x Congo. Plot size was 20 m x 4 m The size of planting hole was 0 6 m x 0 6 m x 0.6 m. one plant per hole. Canle manure mixed with soil was applied at planting lime Results showed that capok with plant spacing of 2 m x I m produced higher number of active buds per ha ( 147 625 buds) than that with plant spacing of 2 m x 2 m (79 661 buds). However, ihe first plant spacing produced smaller diameter (34.47 mm) than the second one (42.53 mm) The highest number of active buds was produced by the clone SS 29 x C, i.e. 123 959.33 buds per ha or 33.33 buds per plant